Kesetiaan dalam Penderitaan: Analisis Naratif dan Teologis Ayub 1:1-22 serta Relevansinya bagi Orang Kristen Masa Kini - Magdalena Ayang Tura; Hagar Magdalena Oujaha; Malik Bambangan (Pusat Riset dan Inovasi Nasional, 2025)
This article explores the theme of faithfulness amid suffering through a narrative and theological analysis of Job 1:1–22, while also examining its relevance for the Christian faith today. Job is chosen as the central figure due to his portrayal in the Bible as a man who endured extreme suffering yet maintained his spiritual integrity. This research uses a qualitative approach with a library research method, analyzing biblical texts and relevant theological literature. The study focuses on understanding suffering as a test of faith allowed by God, rather than as punishment for sin. The analysis reveals that Job is portrayed as a righteous, upright, God-fearing man who shunned evil. In Job 1:1–22, he loses all his wealth and children in a very short time, yet continues to submit to God’s will. His well-known declaration, “The Lord gave, and the Lord has taken away; blessed be the name of the Lord,” affirms the depth of his faith and obedience. Job’s faithfulness is not transactional, but emerges from a pure spiritual relationship with God. Job’s story remains highly relevant for contemporary Christians. In today’s world filled with adversity, Job teaches that suffering is not necessarily a sign of wrongdoing or lack of faith, but can be a means for spiritual growth and character formation. This article affirms that true faith will remain steadfast even when tested by suffering. Thus, Job stands as an enduring example of unwavering faithfulness to God in the face of deep crisis.